Influence of Leadership Style, Work Motivation, Working Conditions on the Performance of Population and Civil Registration Service Employees in Jepara Regency - Ainur Rizqiyana, Dina Laila; Imron, Much (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: The research aims to examine the influence of leadership style, work motivation, and working conditions on the performance of employees at the Civil Registration Office in Jepara Regency. Methodology: This study A quantitative approach using a saturated sampling or census technique. The population consisted of 72 employees, with 57 respondents the criteria for inclusion in the sample. Data analysis the IBM SPSS Statistics 25. Results: The studyâ€™s findingÂ  indicate that leadership style variable does not significantly affect employee performance. Meanwhile, work motivation and working conditions have a positive influence which is proven to significantly affect the improvement of employee performance. Findings: The provide new insights to improve employee performance in the public service sector. Novelty and Originality: This study provides an important contribution to the development of human resources in local government in the context of public services. The findings provide new insights that can be used to improve employee performance in the public service sector.Conclusion : Work motivation and working conditions positively influence employee performance, whereas leadership style does not have a significant impact. The implications highlight the importance of focusing on improving motivation and working conditions as strategies for enhancing employee performance. Type of Paper: Research paper.